2021
DOI: 10.1136/jitc-2020-002051
|View full text |Cite
|
Sign up to set email alerts
|

CD122-directed interleukin-2 treatment mechanisms in bladder cancer differ from αPD-L1 and include tissue-selective γδ T cell activation

Abstract: BackgroundAnti-programmed death-ligand 1 (αPD-L1) immunotherapy is approved to treat bladder cancer (BC) but is effective in <30% of patients. Interleukin (IL)-2/αIL-2 complexes (IL-2c) that preferentially target IL-2 receptor β (CD122) augment CD8+ antitumor T cells known to improve αPD-L1 efficacy. We hypothesized that the tumor microenvironment, including local immune cells in primary versus metastatic BC, differentially affects immunotherapy responses and that IL-2c effects could differ from, and thus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…We previously reported that CD122-targeting IL-2c activated γδ T cells but not CD8 + T cells to treat orthotopic MB49 BC. 20 However, effects on other CD122 + immune cell populations in bladder are unreported. Like MB49, we observed reduced tumor growth and tumor weight in IL-2c treated mice bearing orthotopic MBT-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that CD122-targeting IL-2c activated γδ T cells but not CD8 + T cells to treat orthotopic MB49 BC. 20 However, effects on other CD122 + immune cell populations in bladder are unreported. Like MB49, we observed reduced tumor growth and tumor weight in IL-2c treated mice bearing orthotopic MBT-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note: We previously reported data showing survival of isotype-treated mice bearing orthotopic MB49. 20 Eomes, Eomesodermin. IL-2c, interleukin-2 complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations